Global careers - Harris, Hilary; Dickmann, Michael (Journal of management development, 2004)
This special edition is the result of a colloquium on global careers held by the Centre for Research into the Management of Expatriation (CRE ̀ME) at Cranfield School of Management. Academics and practitioners came together for two days to share the latest thinking and to design an international research project into this critical aspect of international management. Previously published in: Management Development, Volume 23, Number 9, 2004.